Does family composition affect social networking? - Odelia Heizler; Ayal Kimhi (Institute for the Study of Labor (IZA), 2012)
This paper analyzes the effect of family composition, and in particular the number of children, the age gap between the oldest and youngest child and the age of the youngest child, on parents' involvement in social networks. The predictions of a simple theoretical model are confirmed by an empirical analysis of Israeli Social Survey data for 2002-2006. The number of children has a U -shaped effect on parents' involvement in social networks, with substantial differences between fathers and mothers. The negative effect is dominant on the mothers' involvement in social networks, while the positive effect is dominant on the father's involvement in social networks. The age gap between children has a positive effect on both parents' involvement in social networks, while the age of the youngest child has a positive effect on the father's involvement in social networks. These results imply that social network considerations might be important for fertility decisions.
urn:nbn:de:101:1-201206146555
Keywords: J12; J13; D85; 330; social networks; family composition; children; Familiensoziologie; Väter; Mütter; Soziales Netzwerk; Israel